Estimates, temporal evolution, and drivers of the global burden of cardiovascular disease attributable to particulate matter air pollution, 1990–2021: A systematic analysis from the global burden of disease study 2021 - Shuailing Liu; Huajie Yang; Mingzheng Li; Yinchu Guo; Zhaoqi Zhang; Wei Liu; Shuo Wu; Tong Liu; Shenghang Li; Juexin Zhang; Yuejia Wang; Luoxin Li; et al. (Ecotoxicology and Environmental Safety)
Cardiovascular diseases (CVDs) are the most common non-communicable diseases worldwide. Fine particulate matter (PM2.5) has emerged as a significant modifiable risk factor contributing to the burden of CVDs. This study examines the global burden of CVDs attributable to PM2.5 pollution from 1990 to 2021. Using data from the Global Burden of Disease (GBD) study. We calculated the estimated annual percentage change (EAPC) via log-linear regression and assessed age-standardized rates (ASRs, per 100,000 population) for deaths and disability-adjusted life years (DALYs). While global ASRs for PM2.5-related DALYs declined from 2009.92 to 1161.77 per 100,000, these reductions were unequal: high-income regions, such as North America and Western Europe, achieved substantial progress, whereas low-income regions, particularly Sub-Saharan Africa and South Asia, faced rising burdens from PM2.5 exposure. The study highlights the shift from household to ambient sources of PM2.5 as the main contributor to CVDs, particularly in rapidly industrializing regions, with the total DALYs attributable to PM2.5 increasing from 78.87 million in 1990–99.64 million in 2021. Decomposition analysis identifies population growth, aging, and epidemiological changes as key drivers of the global trends. This study provides evidence-based guidance for the CVDs prevention and PM2.5 air pollution policy.